1967
DOI: 10.1063/1.1709772
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation Damping in Aluminum at High Strain Rates

Abstract: Impact shmr tests of the Kolsky Thin Hafer type vere used. to determine tho effect of temperature and strain-rate on the critical resolved shear stress for slip in aluminu..""n sin3le crystals at strain-rates of 10 4 scc-1 and in the temperature range 20°K to 500°K. The aluminum deformed in a .vi:..>cous•rnanner in that the flow stress was proportional to the plastic strain-rate. The behavior was found to be temperature dependent. The results were discussed in terms of dislocation damping models• I•:J:-.ere fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

1968
1968
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…[4][5][6][7][8] In general, the results show that, to a greater or lesser extent, most non-metallic and composite materials exhibit a significant change in mechanical properties when deformed under different strain rates and temperatures. Several mechanisms have been proposed to account for the change in mechanical properties prompted by high velocity deformation, including dislocation damping, 9) thermally-activated mechanisms, 10) and so on. However, to obtain a broader understanding of the effects of the deformation temperature and strain rate on the mechanical response of engineering materials, a comprehensive temperature-dependent analysis is required.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8] In general, the results show that, to a greater or lesser extent, most non-metallic and composite materials exhibit a significant change in mechanical properties when deformed under different strain rates and temperatures. Several mechanisms have been proposed to account for the change in mechanical properties prompted by high velocity deformation, including dislocation damping, 9) thermally-activated mechanisms, 10) and so on. However, to obtain a broader understanding of the effects of the deformation temperature and strain rate on the mechanical response of engineering materials, a comprehensive temperature-dependent analysis is required.…”
Section: Introductionmentioning
confidence: 99%
“…Above the transition strain rate, the flow stress is assumed to be drag controlled [23]. Stress and strain rate in this regime is linear and expressed by Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Tirupataiah [22] has further constructed the transition strain rates for a number of metals and showed that the transition strain rate for common metals and alloys lies between 102 and 104 s À1 . Before the transition strain rate, it is usually assumed that the deformation is controlled by the thermally activated deformation mechanism [23] and a logarithmic relation between stress and strain rate is usually found in this regime as,…”
Section: Discussionmentioning
confidence: 99%
“…1113) Several mechanisms have been proposed to account for the change in mechanical properties prompted by high velocity deformation, including dislocation damping, 14) thermal activation 15) and dislocation generation. 16) Many studies have shown that high strain rate loading induces microstructural evolution and phase transformation, and therefore has a significant effect on the material properties.…”
Section: Introductionmentioning
confidence: 99%